Education, neuroscience, and types of creativity - Arne Dietrich; Sandra Zakka (Future in Educational Research)
Abstract The concept of multiple intelligences has taken hold in education. The idea that there are different types of intelligence for different domains helps inform educational approaches to learning and development. Evidence in creativity research, particularly from neuroscience, is accumulating that there are also different types of creativity. This, however, has not been the predominant way neuroscience has approached creativity. Consequently, the idea of different types of creativity has also not yet taken hold in education. Despite psychology regarding creativity as being made up of many complex, multifaceted, and varied cognitive and emotional processes deployed across many different domains, we still think of, and test, creativity as if it were a single, separate, cohesive, and discrete thing. Having perseverated on experimental paradigms that are theoretically and conceptually incoherent, this paper explains why empirical neuroscience research has failed to identify and distinguish different types of creativity. This is particularly important because neuroscience can take a lead in establishing the idea of multiple creativity types. The paper then outlines the negative implications for education if creativity is continuously being treated as a single faculty or monolithic entity. Finally, the paper introduces a division of creativity into three types that could result in a more individual approach to teaching and promoting creativity in classrooms.